PENYULUHAN MENGENAI PENGELOLAAN SAMPAH TERHADAP KELOMPOK TPS3R SADU KENCANA DI DESA DAUH PEKEN - Ni Made Serma Wati; Gusti Ayu Gede Sukraningsih; I Gusti Ayu Surya Utami (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
Waste in Indonesia is a persistent problem. The amount of waste generated fluctuates over time. Surging waste volumes, if not managed wisely, have the potential to have significant negative impacts on the environment and human health. Dauh Peken Village, Tabanan District, Tabanan Regency, is a village in the center of Tabanan City, experiencing problems with waste management. Based on a situational analysis, public awareness of waste management remains very low. Meanwhile, domestic waste generated by non-business household activities is increasing. Recognizing the urgency of this problem, this community partnership empowerment activity aims to provide the community with an understanding of organic waste management methods. The activity also aims to educate participants on how to create digital posters, with the aim of disseminating and encouraging the wider community to sort and process waste wisely. The targeted partner for this program is the Sadu Kencana Waste Management Unit (TPS3R) group located in Dauh Peken Village, Tabanan, Bali. The community partnership empowerment activity involves several stages: preparation, implementation, and evaluation. The community service activities were implemented through several methods, including the dissemination of materials on digital poster creation, waste management awareness campaigns, and organic waste processing practices. The program ran smoothly, with excellent participant participation and enthusiasm. This community service program achieved its goal of increasing participants' knowledge and understanding of digital posters and organic waste processing methods.